Access to and use of health and social care services for people with learning disabilities during COVID-19: a longitudinal study. Issue 1 (24th January 2022) - Flynn, Samantha; Hatton, Chris; Hastings, Richard P.; Hayden, Nikita; Caton, Sue; Heslop, Pauline; Jahoda, Andrew; Todd, Stuart; Oloidi, Edward; Beyer, Stephen; Mulhall, Peter; Taggart, Laurence
Abstract : Purpose: This paper aims to present data about access to and use of health and social care services by adults with learning disabilities during the COVID-19 pandemic in England, Northern Ireland, Scotland and Wales. Design/methodology/approach: Data were collected in three waves between December 2020 and September 2021 and concerned the use of health and social care services during the COVID-19 pandemic. Data were collected at one or more time-points directly from 694 adults with learning disabilities and through separate proxy reports by family carers and paid support staff of another 447 adults with learning disabilities. Findings: Many people with learning disabilities who reported regularly accessing services/supports pre-pandemic were not receiving them during the timeframe of this study. There were indications of increasing access to some services and supports between Wave 2 and 3, but this was not universal. Practical implications: People in Cohort 2, who were likely to have severe/profound learning disabilities, were less frequently reported to access online community activities than people in Cohort 1, which is likely to exacerbate existing social isolation for this cohort and their family carers. Service providers should seek to ensure equitable access to services and activities for all people with learning disabilities in the event of future lockdowns or pandemics. Originality/value: This is the largest longitudinal study about the impact of the COVID-19 pandemic on health and social care services for adults with learning disabilities in the UK. We primarily collected data directly from adults with learning disabilities and worked with partner organisations of people with learning disabilities and family members throughout the study.